Home advantage in skeleton: Familiarity versus crowd support - Chun, S.; Park, S. S. (Journal of Sports Economics, 2021)
The paper investigates home advantages in skeleton. Our study broadens home advantage literature by providing models and estimation strategy applicable to other individual sports with tracks or courses such as biathlon, cross country skiing, etc. We identified two sources of advantages: support from the crowd; familiarity with the track. In the Olympics and the World Championships, home advantage leads to about a 0.510% improvement in performance on average, of which 0.110%-points are due to crowd support and 0.401%-points due to familiarity. Out-contribution of familiarity effect is common in all six major skeleton series.